Long-term antibiotics for prevention of recurrent urinary tract infection in older adults: systematic review and meta-analysis of randomised trials. - Ahmed, H; Davies, F; Francis, N; Farewell, D; Butler, C; Paranjothy, S (BMJ Publishing Group, 2017)
Objective To address clinical uncertainties about the effectiveness and safety of long-term antibiotic therapy for preventing recurrent urinary tract infections (UTIs) in older adults. Design Systematic review andmeta-analysis of randomised trials. Method We searched Medline, Embase, The Cumulative Index to Nursing and Allied Health Literature(CINAHL), and the Cochrane Register of Controlled Trials from inception to August 2016. Eligible studies compared long-term antibiotic therapy with non-antibiotic therapy or placebo in men or women aged over 65, or in postmenopausal women, with recurrent UTIs. Results We did not identify any studies that included older men. Three randomised controlled trials compared long-term antibiotics with vaginal oestrogens (n=150), oral lactobacilli (n=238) and D-mannose powder (n=94) in postmenopausal women. Long-term antibiotics reduced the risk of UTI recurrence by 24% (three trials, n=482; pooled risk ratio (RR) 0.76; 95% CI 0.61 to 0.95, number needed to treat=8.5). There was no statistically significant increase in risk of adverse events (mild adverse events: pooled RR 1.52; 95% CI 0.76 to 3.03; serious adverse events: pooled RR 0.90, 95% CI 0.31 to 2.66). One trial showed 90% of urinary and faecal Escherichia coli isolates were resistant to trimethoprim–sulfamethoxazole after 1 month of prophylaxis. Conclusions Findings from three small trials with relatively short follow-up periods suggest long-term antibiotic therapy reduces the risk of recurrence in postmenopausal women with recurrent UTI. We did not identify any evidence to inform several clinically important scenarios including, benefits and harms in older men or frail care home residents, optimal duration of prophylaxis, recurrence rates once prophylaxis stops and effects on urinary antibiotic resistance.